A review on the fluid structure interaction of circular plates using numerical methods - Anju V Nair; Abdul Rahman Mohd Kasim; Mohd Zuki Salleh (Research and Social Study Institute, 2022)
Fluid structure interaction is a nonlinear multi physics phenomenon that have wide range of applications in science and engineering fields. This article presents the development of numerical methods to solve the fluid structure interaction problem deals with the vibration analysis of plate structures in contact with fluid. The modeling of fluid and structure are essential to study the fluid structure interaction problems. The development of suitable mathematical models and their validation are discussed herewith.